2018
DOI: 10.3341/kjo.2018.0011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-vascular Endothelial Growth Factor Treatment of Retinopathy of Prematurity: Efficacy, Safety, and Anatomical Outcomes

Abstract: PurposeTo investigate the efficacy, safety, and anatomical outcomes associated with intravitreal anti-vascular endothelial growth factor (VEGF) treatment of retinopathy of prematurity (ROP).MethodsWe performed a retrospective review of intravitreal anti-VEGF (bevacizumab or ranibizumab) treatment of 153 eyes (83 infants) diagnosed with ROP at two tertiary hospitals from June 2011 to January 2017. The primary outcome was the rate of recurrence requiring additional treatment; secondary outcomes included incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 38 publications
2
13
0
2
Order By: Relevance
“…Although uncommon, some complications such as cataract, vitreous hemorrhage, corneal abrasion/opacity, endophthalmitis, hyphema, and thromboembolic events may develop after bevacizumab injection (29). As in our study, there are publications reporting no complications after IVI (30,31).…”
Section: Discussionsupporting
confidence: 69%
“…Although uncommon, some complications such as cataract, vitreous hemorrhage, corneal abrasion/opacity, endophthalmitis, hyphema, and thromboembolic events may develop after bevacizumab injection (29). As in our study, there are publications reporting no complications after IVI (30,31).…”
Section: Discussionsupporting
confidence: 69%
“…The therapeutic treatment of ROP is particularly challenged by the use of invasive anti-RNV therapies often resulting in the blockade of normal postnatal retinal vasculogenesis and damage to the neuroretina [53]. The results of our studies demonstrate that UDCA can halt pathological neovascularization in the ischemic postnatal retina without affecting normal vascular growth or provoking systemic toxicity ( Figure S2), thus satisfying two very important characteristics of a drug candidate for the treatment of ROP.…”
Section: Discussionsupporting
confidence: 58%
“…[7][8][9] However, the effects of this intervention are relatively short term, while its long-term complications remain unclear, such as postoperative refractive errors. Kang et al 10 showed that anti-VEGF drugs do not cause refractive errors after ROP treatment, while Kabataş et al 11 found that effects of the intravitreal injection of anti-VEGF drugs did not differ significantly from those of laser photocoagulation, with both potentially causing refractive errors.…”
Section: Introductionmentioning
confidence: 99%